Modelagem Computacional da Propagação Acústica Proveniente de Fontes Multifrequênciais Usando Guias Digitais de Ondas - Boaventura, Ana Paula Freitas Vilela (2009)
The goal of this research is the creation of virtual acoustic environments, in this context, was constructed a computational tool, aiming to the acoustic modeling of reverberation environment. In this way, it was necessary to elaborate a numerical system able to simulate the wave sound propagation and, mainly its interactions with the surfaces encountered in the analyses. These interactions represent the basic wave phenomena, as reflection, transmission and absorption of sound waves by the obstacles. To obtain these objectives with this numerical model, it is necessary to separate into three important elements: the sound source, the room acoustic, and the listener, in this case, the receiver. Room acoustic modeling techniques can be divided into, for example, geometry-base and wave-based. In this work, a specific wave-base method has been adopted, the digital waveguide mesh. This methodology is a numerical system based on the known d Alembert solution for the General Wave Equation. The advantage of this method is that it can be easily describe the one-dimensional sound wave propagations between any two points in the space. The meshes created are, actually, digital waveguide interconnected, defining different geometries of mesh, as square, triangular, and others, for the 2D and for example cubic, for the 3D case. The information is captured in some points of interconnection of the waveguides, called scattering junctions. The whole formulation is based on the impedance properties of the environment. At particular, the waveguide technique is efficiency, by simplicity of algorithm, and by good results obtained for simulated Multifrequencial sources. To obtain a friendly interface, the code was written with a Language Object Oriented.